Analys av dagens och framtidens koldioxidemissioner längs Europaväg 39 - en del av det norska projektet Ferjefri E39 - Axelsson, Lovisa; Blom, Evelin; Kastari, Simon; Khairallah, Vania; Norenius, David; Söderstjerna Jörgensson, Sabina (My University, 2015)
The project Ferjefri E39 aims to make the E39-route between Kristiansand and Trondheim free from ferries and, despite of an expected increase in traffic volumes, reduce the carbon dioxide emissions from the road. In this report, different vehicle technologies have been compared with respect to energy consumption, CO2-emissions, efficiency and cost. Currently Norwar is investing in electrical vehicles and the main focus in this report is therefore on electrical vehicles and electrification of the road. A change towards an electrified vehicle fleet could cause problems with, for example, new peaks for electricity and power demand. Plug-in-hybrid electric vehicles could be a possible transition towards a vehicle fleet free from fossil fuels. However, the batteries required with regard to range and weight are today not applicable for heavier vehicles. Biofuel could be used by all vehicle types, but are a limited resource phasing problems with competition from other energy sectors and from food production. Electric vehicles that utilize electricity produced from a fuel cell is another possible technology, with the main benefit of only emitting steam when operated. But fuel cells are today more expensive compared to other alternative vehicle technologies. In order to get a general overview of how these vehicle technologies might affect the demand for electricity in E39-region, the energy consumption and carbon dioxide emissions from the E39 has been calculated. This was done by creating a fuel consumption model based on known physical and empirical relations. The input parameters used in the model were based on road and fuel properties, and different vehicle parameters. The current carbon dioxide emissions from E39 were calculated to 0.75 Mt and are expected to increase with 90 % until 2060 if fossil fuels continue to dominate the market. If, however, a transition to alternative technologies investigated in this study, takes place, there is a possibility to reduce the emissions with 100 %. A complete transition to electricity would be the most energy efficient alternative, and the traffic on E39 would require 3.25 TWh in year 2060, which is only an increase of 0.3 TWh compared with the current usage, in spite of the large increase in the number of vehicles. An entire enforcement of bioenergy requires 5.42 TWh year 2060 and fossil fuel that requires 5.85 TWh. In order to see if this energy consumption 2060 could be covered by energy generated along the road, an investigation of the electricity and biofuel potential in the region was done. Energy generated from wind in the fjords covers only 9.6 % of the E39 energy consumption 2060 when the road is completely electrified. The corresponding number for solar energy is 11.8 %. However, the potential for bioenergy might be able, considering competition with other sectors, to cover parts of the energy demand for E39. But if also considering biofuel production from algae, a technology that today is under development, a larger part of the energy demand for E39 could come from biofuels. Ferjefri E39 is a multidimensional project with many perspectives to consider, and an introduction of several vehicle technologies might be needed in order to reduce the carbon dioxide emissions.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering